Accessing to the industry 4.0 to support Vietnam to achieve the goal of an industrial coutry - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
This research confirmed that the most fundamental of the nature of Industry 4.0 (I4.0) is to recognize properly the importance, opportunities, advantages and disadvantages of this revolution and make some comments, assessments and forecasts on Vietnam’s scenarios and addressed a number of issues for the management of science and technology (S&T) activities and make more objective, active and active in responding to new waves of new technologies that impact on changing management awareness, management tools and management practices of S&T activities in Vietnam. To achieve Vietnam’s goal of becoming an industrial country soon, the article also proposes a number of proposals to approach I 4.0 by acting in an active, creative and flexible manner which are suitable to the current conditions in our country. Code: 17121101